Composition of lymphocyte subpopulations in normal canine lymph nodes. (15th December 2014) - Rütgen, Barbara C.; König, Ramona; Hammer, Sabine E.; Groiss, Sandra; Saalmüller, Armin; Schwendenwein, Ilse
<x xml:space="preserve">Abstract</x> Background Flow cytometric immunophenotyping of lymph node aspirates has become a standard practice of canine lymphoma diagnostic workup. Ultimately, the combination of flow cytometry data, histopathology, and clinical signs allows consensus classification, and improves prognostic accuracy and therapeutic approaches. Objectives Although there is a growing body of information regarding lymphocyte population subsets in various types of lymphoma, only few studies provide information regarding the composition of the normal canine lymph node. The aim of this prospective study was to establish exploratory reference data for lymphocyte subpopulations in normal canine lymph nodes using an extended panel of antibodies. Methods Popliteal lymph nodes excised from normal dogs were analyzed by cytology, multi‐color flow cytometry using 11 different canine‐specific and anti‐human cross‐reactive monoclonal antibodies, and polymerase chain reaction for antigen receptor rearrangement (PARR). Results Subpopulations from lymph nodes of 26 dogs were classified according to the following positive antibody reactions: CD11a+ 92.2 ± 12.3%, CD3+ 55.0 ± 14.1%, CD3‐12+ 57.3 ± 14%, CD5+ 52.3 ± 12.7%, CD21+ 33.9 ± 11.8%, CD79αcγ+ 46.9 ± 14.8%, CD56+ 4.9 ± 5.9%, and CD14+ 5.5 ± 6.8%. There were 58.7 ± 9% CD4+ and 21.3 ± 7.8% CD8+ cells inside the gate of CD3+ cells. Cytology revealed a mixed population of mostly lymphoid cells in all samples. The absence of a monoclonal or oligoclonal neoplastic population was confirmed by PARR. Conclusion This study establishes for the first time flow cytometry data of lymphocyte populations in a larger group of normal canine lymph nodes, including populations positive for some new antibodies against CD3‐12, CD5, CD11a, CD56, and CD79αcy.